Spremljanje kakovosti zapisov dnevne produkcije v COBIB.SI v obdobju od 2015 do 2020 - Badovinac, Branka (Organizacija znanja, 2021)
In this paper, the results of an analysis of the data quality performed within quality control of daily bibliographic records production in the period from 2015 to 2020 are presented. The sample included 13,478 bibliographic records with associated authority records. The analysis is based on the data quality dimensions that were attributed to the recorded errors of the reviewed bibliographic and normative records. Also, the individual errors in the context of specific data elements are presented. Furthermore, the results include an indicative quality score of records in terms of the number of messages sent to cataloguers and the performance of the monitoring method in terms of the proportion of records corrected. According to our estimations, some 70% of the records reviewed were good or good enough and the response rate of cataloguers was relatively high. In the discussion, problems with some data elements were highlighted and it was stressed how important it is to keep up to date with changes in the Slovenian cataloguing practice.
Keywords: 2015-2020; authority records; bibliografski zapisi; bibliographic records; COBIB.SI; data quality; kakovost podatkov; normativni zapisi; quality control of daily production; spremljanje kakovosti dnevne produkcije